2020
DOI: 10.1111/jam.14736
|View full text |Cite
|
Sign up to set email alerts
|

γ‐aminobutyric acid production by Kluyveromyces marxianus strains

Abstract: Aims Kluyveromyces marxianus dairy strains were tested for γ‐aminobutyric acid (GABA) production. The genes involved in GABA catabolism (UGA1 and UGA2) and anabolism (GAD1) were found in K. marxianus genome. Their relative expression was evaluated with primer designed ad hoc. Methods and Results Strains were grouped on the basis of GAD1 gene sequence. Representative strains for each group were tested for GABA production by high‐performance liquid chromatography. All strains produced it at low levels. qRT‐PCR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The production of GABA for the strains in yeast extract peptone dextrose medium with MSG 10 mm incubated at 27 • C, varied from 2.54 mg/L to 7.78 mg/L (0.025 and 0.075 mM, respectively), which is much lower than the levels found in the two K. lactis isolates in this study: 1.65 mM for BIOTEC009 and 0.31 mM for BIOTEC010. In this respect, polymorphisms in the genes coding for glutamate decarboxylase are responsible for variations in GABA production of strains even between the same species [46]. Finally, note that L. pseudomesenteroides BIOTEC012 was one of the microorganisms that produced the most GABA content (1.18 mM).…”
Section: Psychobiotic Potential Through Gaba Production Assaymentioning
confidence: 96%
“…The production of GABA for the strains in yeast extract peptone dextrose medium with MSG 10 mm incubated at 27 • C, varied from 2.54 mg/L to 7.78 mg/L (0.025 and 0.075 mM, respectively), which is much lower than the levels found in the two K. lactis isolates in this study: 1.65 mM for BIOTEC009 and 0.31 mM for BIOTEC010. In this respect, polymorphisms in the genes coding for glutamate decarboxylase are responsible for variations in GABA production of strains even between the same species [46]. Finally, note that L. pseudomesenteroides BIOTEC012 was one of the microorganisms that produced the most GABA content (1.18 mM).…”
Section: Psychobiotic Potential Through Gaba Production Assaymentioning
confidence: 96%
“…Glutamic acid decarboxylase has also been identified in yeasts such as Saccharomyces cerevisiae and Kluyveromyces marxianus isolated from fermented product [16,45]. S. cerevisiae had lower activity than L. plantarum, this may be caused by the utilization of GABA by S. cerevisiae as nitrogen source [16,18].…”
Section: γ-Aminobutyric Acid Metabolic Pathwaymentioning
confidence: 99%
“…GABA occurs naturally in many plant foods, and is present at high levels in fermented products, especially fermented dairy products ( Diana et al, 2014 ; Park et al, 2021 ). Since lactic acid bacteria (LAB) are recognized as safe microorganisms, most studies have focused on their GABA production capacity ( Perpetuini et al, 2020 ). However, few studies have focused on yeast, even though these strains play an important role in the production wine, bread, dairy products and many other fermented foods ( Hittinger et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast have ability to metabolize proteins, lipids and organic acids, allowing it to grow on the surface of cheese and promote the formation of cheese flavor and texture ( Perkins et al, 2020 ). Sechi reported that the GABA production of Saccharomyces cerevisiae JBCC-A74 was 0.33 g/L ( Sechi et al, 2014 ), whereas Perpetuini et al (2020) demonstrated that the GABA production of Kluyveromyces marxianus K326 was 7.78 ± 1.88 mg/L.…”
Section: Introductionmentioning
confidence: 99%